Novel IFT122 mutation associated with impaired ciliogenesis and cranioectodermal dysplasia. Issue 2 (10th December 2013) - Alazami, Anas M.; Seidahmed, Mohammed Zain; Alzahrani, Fatema; Mohammed, Adam O.; Alkuraya, Fowzan S.
Abstract Cranioectodermal dysplasia (CED) is a very rare autosomal recessive disorder characterized by a recognizable craniofacial profile in addition to ectodermal manifestations involving the skin, hair, and teeth. Four genes are known to be mutated in this disorder, all involved in the ciliary intraflagellar transport confirming that CED is a ciliopathy. In a multiplex consanguineous family with typical CED features in addition to intellectual disability and severe cutis laxa, we used autozygosity‐guided candidate gene analysis to identify a novel homozygous mutation in IFT122, and demonstrated impaired ciliogenesis in patient fibroblasts. This report on IFT122 broadens the phenotype of CED and expands its allelic heterogeneity.